Characterization of the Body Composition of the Male Boyacá FIFA Futsal Team Players (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2017)
The objective of the present study was to characterize the body composition of the male Boyacá FIFA futsal team players. A total of 14 athletes participated, with an average age of 25.1 years, a weight of 69.7 kg, and a height of 171.5 cm. The team exhibited a balanced mesomorphic somatotype, with a predominance of the muscular component over fat. The study shows that the players have an optimal somatotype for competition and provides updated biotypological reference data for the competitive futsal population.